2015
DOI: 10.4097/kjae.2015.68.6.603
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided central cluster approach for the supraclavicular brachial plexus block: a case series

Abstract: There are many different approaches to ultrasound-guided supraclavicular brachial plexus block (US-SCBPB), and each has a different success rate and complications. The most commonly performed US-SCBPB is the corner pocket approach in which the needle is advanced very close to the subclavian artery and pleura. Therefore, it may be associated with a risk of subclavian artery puncture or pneumothorax. We advanced the needle into the central part of the neural cluster after penetrating the sheath of the brachial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Early papers of ultrasound guidance described the brachial plexus as a ‘cluster of hypoechoic nodules’ or as a main and other satellite ‘neural clusters’ [ 14 , 17 ]. During targeted intracluster injection, the needle is advanced within the sheath containing one or more clusters of hypoechoic neurologic elements, and the local anesthetic is injected inside the clusters [ 18 , 19 ]. The nerve structures were approached as a group, without distinguishing the identity and location of each individual trunk due to relatively low qualities of ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Early papers of ultrasound guidance described the brachial plexus as a ‘cluster of hypoechoic nodules’ or as a main and other satellite ‘neural clusters’ [ 14 , 17 ]. During targeted intracluster injection, the needle is advanced within the sheath containing one or more clusters of hypoechoic neurologic elements, and the local anesthetic is injected inside the clusters [ 18 , 19 ]. The nerve structures were approached as a group, without distinguishing the identity and location of each individual trunk due to relatively low qualities of ultrasound imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sensory-motor test evaluations were performed by an independent blinded observer. Therefore, we believe that unintentional bias had little impact on the overall results (12).…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 94%
“…Lee et al demonstrated in a series of 51 patients that single injection of LA into the central cluster of the supraclavicular brachial plexus was associated with a success rate of 92.2% (47 out of 51 patients needed no LA supplementation for hand and forearm surgery) [16] (Fig. 4).…”
Section: Upper Limb Brachial Plexus Blocksmentioning
confidence: 99%